Tingkat Kesadaran Masyarakat dalam Membayar Zakat Fitrah: Studi Kasus di RT 05 Dusun Nglorog, Desa Mojopuro, Kecamatan Jatiroto, Kabupaten Wonogiri - Meidiana Safitri; Harianti Fauziyatul Izah; Muhamad Ridho; Fauzun Jamal (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Public awareness of paying zakat fitrah is an important indicator of religious understanding and social responsibility, but in practice it is often not optimal at the local community level. This study aims to examine the level of awareness of the community of RT 05, Nglorog Hamlet, Mojopuro Village, Wonogiri Regency, in paying zakat fitrah and the factors that influence it. The research method used was descriptive qualitative with data collection through observation, in-depth interviews, and literature study. The results showed that most people regularly pay zakat fitrah, but their understanding of other productive zakat is still limited. Factors such as knowledge, religiosity, economic conditions, and the existence of professional local zakat institutions were found to influence public awareness. Interactive education, seminars, door-to-door approaches, and the establishment of Zakat Management Units (UPZ) significantly increased zakat literacy, trust in zakat management, and community participation. In conclusion, strengthening village-based zakat institutions and contextual educational approaches can increase awareness of zakat fitrah while maximizing the socio-economic potential of zakat for community empowerment.